2020
DOI: 10.1002/ente.202000210
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrocatalytic Oxidation of Methanol on Pt‐Decorated Bi2WO6/Graphene Nanosheets with Visible Light Assistance

Abstract: Noble metal/semiconductor–based electrocatalysts have been proverbially used as the anode material in direct methanol fuel cells (DMFCs) recently. Combined with the advantage of the properties of noble metals and semiconductors, photo‐assisted electrocatalytic methanol oxidation is a valid route to increase the catalytic activity of catalysts in DMFCs. Herein, a 2D composite of bismuth tungstate/reduced graphene oxide (Bi2WO6/RGO) with excellent optical, electrical, and thermal stability is used as the support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…So the CoS x /NiS x (4 : 1) heterojunction was use for the following investigation. According to the previous report, [9] the light‐to‐current efficiency ( η ) can be used for illustrating the photocurrent contributes to the efficiency of the fuel cell. The η of CoS x /NiS x heterojunction can be expressed by equation (1), where J PEC and J EC represent the current densities of CoS x /NiS x with and without light at 0.6 V. trueη=JPEC-JECJPEC×1001.111pt% …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So the CoS x /NiS x (4 : 1) heterojunction was use for the following investigation. According to the previous report, [9] the light‐to‐current efficiency ( η ) can be used for illustrating the photocurrent contributes to the efficiency of the fuel cell. The η of CoS x /NiS x heterojunction can be expressed by equation (1), where J PEC and J EC represent the current densities of CoS x /NiS x with and without light at 0.6 V. trueη=JPEC-JECJPEC×1001.111pt% …”
Section: Resultsmentioning
confidence: 99%
“…Previous report [4] indicated that, the active oxygen sources (e. g., O ads and OH ads ) from the dissociation of water is one of the prerequisites to oxidize intermediate CO ads . In order to improve the efficiency of water dissociation, semiconductor materials, such as TiO 2 , [5] WO 3 , [6] CdS, [7] C 3 N 4 , [8] Bi 2 WO 6, [9] and ZnO, [10] have been certified as promising support for Pt and other precious metal (Au and so on) electrocatalyst because of the excellent photoelectronic properties and enhanced photoelectrocatalytic water dissociation activity. In such photo‐assisted fuel cell system, the methanol molecules are oxidized at the surface of a noble metal/semiconductor anode through synergistic electrocatalytic and photocatalytic routes under light illumination.…”
Section: Introductionmentioning
confidence: 99%
“…42 These properties contribute to the visible-light harvesting ability and high charge mobility of metal sulfides. 43,44 According to the previous report, 45 the light-to-current efficiency (Z) can be used for illustrating the photocurrent contributes to the efficiency of the fuel cell. The Z of CoS x can be expressed by eqn (1), where J PEC and J EC represent the current densities of CoS x with and without light irradiation at 0.6 V, respectively.…”
Section: Visible Light-assisted Methanol Electrocatalytic Oxidation P...mentioning
confidence: 99%